Effects of Scapular Proprioceptive Neuromuscular Facilitation Technique on Scapular Dyskinesis - Iqra Altaf, Anam Maqbool, Ayesha Maqbool, Aisha Akram, Saba Iqbal, Zain Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Scapular dyskinesis is termed as improper control of resting position and movement pattern of the scapula having connections with shoulder pain. PNF techniques are the methods of hastening the response of a neuromuscular mechanism through stimulation of proprioceptors. Objective: To find out the effect of scapular proprioceptive neuromuscular facilitation techniques in the treatment of scapular dyskinesis. Methodology: A randomized clinical trial was conducted comprising of 26 patients recruited from District Headquarter Hospital and Aziz Fatimah Hospital, Faisalabad. Patients were randomly allotted into 2 groups. Group A received scapular proprioceptive neuromuscular facilitation and Group B received conventional treatment group. Scapular dyskinesis was assessed through lateral scapular slide test. Visual Analogue Scale and Shoulder pain and Disability Index were used as outcome measures. The treatment was given for four weeks and there were 3 sessions per week. The data was collected at baseline and 4th week post treatment. The data was analyzed by using SPSS software version 23. Results: Within group analysis showed that improvement was observed for pain and shoulder disability in both group A (p=0.000) and group B (p=0.000). Between group analysis revealed significant improvement in pain from 8.23 +1.48 at baseline to 4.08 + 1.60 (p=0.000) and shoulder disability from 97.46+9.19, to 97.46+9.19 (p=0.000) at 4th week post treatment in scapular PNF group. Conclusion: Significant improvement in VAS and SPADI was observed in scapular PNF group as compared to conventional treatment. Keywords: Scapular Dyskinesis, Proprioceptive Neuromuscular Facilitation, Shoulder Pain, Visual Analog Scale